Aneurysmal Patellar Bone Cyst: Case Reportt - Alberto Ramos Gomes; Felipe Neves Campos; Nadiane Maciel Becker; Jan Gabriel Tamanini (Revista Brasileira de Ortopedia, 2019)
Abstract Patellar tumors are rare. Commonly benign, giant-cell tumors and chondroblastomas are the most frequent types of this tumor. Aneurysmal bone cysts are a less common type, corresponding to less than 1% of the cases. The authors present a case of a 23-year-old male patient who presented left patellar pain and swelling for two years. The radiographic images suggested tumoral causes, and the biopsy was negative for neoplasm. The treatment approach was a complete patellectomy, without complications. The imaging follow-up showed no recurrence.